Weber test accuracy in sudden sensorineural hearing loss: which frequency is best?. (4th May 2021) - Ungar, Omer J.; Handzel, Ophir; Oron, Yahav; Warshavsky, Anton; Horowitz, Gilad; Yafit, Daniel; Abu Eta, Rani; Muhanna, Nidal; Shilo, Shahaf
Abstract: Background: Recent guidelines encourage the use of Webet test (WT) as a part of the physical examination of a newly suspected sudden sensorineural hearing loss (SSNHL) patient. However, the most sensitive tuning-fork frequency has never been identified. Objective: To identify the most sensitive frequency for initial WT of patients with suspected SSNHL. Methods: Medical records of patients with confirmed SSNHL, who underwent formal audiometry in which the WT was carried out with different frequencies were analyzed. Results: 319 medical records were identified. The most sensitive WT frequency was 500 Hz, with a sensitivity of 94.49% (223/236. confidence interval 90.76–97.03). There was a non-significant difference between 1000 Hz EBO and 500 Hz EBO ( p  = .1655), a tendency towards a significant difference between 1000 Hz EBO and 2000 Hz EBO ( p  = .0578), and a significantly better sensitivity than the 4000 Hz EBO ( p  = .0163). Conclusion: The most sensitive WT frequency for SSNHL diagnosis is 500 Hz. However, the sensitivity of this frequency is 94.49%. Significance: 512 or 1024 Hz should be used to better identified SSNHL. Even WT lateralization to the affected ear, does not preclude the diagnosis of SSNHL. Formal audiometry should be used in any case of medical history suspected for sudden hearing loss with normal otoscopy.